2020
DOI: 10.7759/cureus.6941
|View full text |Cite
|
Sign up to set email alerts
|

Is Physiologic Stress Test with Imaging Comparable to Anatomic Examination of Coronary Arteries by Coronary Computed Tomography Angiography to Investigate Coronary Artery Disease? – A Systematic Review and Meta-Analysis

Abstract: Coronary computed tomography angiography (CCTA) is a noninvasive diagnostic modality that remains underutilized compared to functional stress testing (ST) for investigating coronary artery disease (CAD). Several patients are misdiagnosed with noncardiac chest pain (CP) that eventually die from a cardiovascular event in subsequent years. We compared CCTA to ST to investigate CP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Several reasons could explain why the event rate was lower than the original estimate, and likely reflects the better diagnostic accuracy of newer high sensitive troponin assays and improvements in the management of patients in the past decade. Greater estimates for relative effect size have been reported in previous trials 8 10 11 30 although our point estimate was similar to a recent meta-analysis, 23 which indicated a hazard ratio for subsequent myocardial Although the lower confidence boundary of the primary endpoint included a clinically meaningful reduction in events, the lack of effect on treatment interventions reinforces our view that early CT coronary angiography is unlikely to influence subsequent myocardial infarction, and a larger trial with greater power would be unlikely to detect a more modest clinically meaningful effect on one year outcomes. Finally, longer term follow-up might identify further benefits in outcomes, especially if preventive treatments are more accurately targeted.…”
Section: Limitations Of the Trialsupporting
confidence: 91%
See 2 more Smart Citations
“…Several reasons could explain why the event rate was lower than the original estimate, and likely reflects the better diagnostic accuracy of newer high sensitive troponin assays and improvements in the management of patients in the past decade. Greater estimates for relative effect size have been reported in previous trials 8 10 11 30 although our point estimate was similar to a recent meta-analysis, 23 which indicated a hazard ratio for subsequent myocardial Although the lower confidence boundary of the primary endpoint included a clinically meaningful reduction in events, the lack of effect on treatment interventions reinforces our view that early CT coronary angiography is unlikely to influence subsequent myocardial infarction, and a larger trial with greater power would be unlikely to detect a more modest clinically meaningful effect on one year outcomes. Finally, longer term follow-up might identify further benefits in outcomes, especially if preventive treatments are more accurately targeted.…”
Section: Limitations Of the Trialsupporting
confidence: 91%
“…Patients valued the use of CT coronary angiography, possibly reflecting a quicker evaluation of their clinical condition and the enhanced diagnostic certainty of the attending clinician. CT coronary angiography was also associated with a reduction in invasive coronary angiography, contrasting with previous trials of acute chest pain where CT coronary angiography was associated with increased rates of invasive angiography 89101123. This disparity likely reflects differences in trial populations, especially the baseline risk and prevalence of coronary heart disease.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“… 38 , 39 Several recent randomised controlled trials have shown that CCTA is associated with a reduced rate of myocardial infarction compared with functional stress testing, and clinical practice guidelines currently endorse the IIA recommendations for CCTA use when stress ECG testing is impractical or stress MPI testing is not evaluable. 40 , 41 , 42 Nevertheless, recent studies have reported that CCTA is associated with increased rates of invasive procedures and high costs with a similar risk of all-cause mortality 38 , 43 , 44 , 45 ; the common use of CCTA seen here should be interpreted with caution. Moreover, the use of scintigraphy was significantly associated with the availability of scintigraphy scanners, suggesting that access to scintigraphy strongly influences the choice of the initial testing strategy.…”
Section: Discussionmentioning
confidence: 70%
“…1 Recent metaanalyses and large prospective randomized clinical trials have demonstrated among other favorable qualities a decrease in subsequent myocardial infarctions and hospital visits compared with functional stress testing in evaluating chest pain in the setting of suspected CAD. [2][3][4] In spite of these results, CCTA is underutilized relative to functional stress testing. To facilitate wider adoption of CCTA, payment amounts should reflect the total cost of providing the test.…”
Section: Introductionmentioning
confidence: 99%